My Injured Brain - Castrodale, Beth (Ars Medica, 2024)
This essay explores how a traumatic brain injury the author suffered several years ago affected her—especially as a reader and writer—and how she managed to return to writing fiction, one of her great passions. The author also considers how the TBI and her family history put her at greater risk of developing dementia and how fears about this risk have shaped her life.